PHYSICAL EDUCATION IN HEALTH WATER TRANSPORT SPECIALISTS - Hodlevskyi, P. M.; Spryn, O. B. (Rehabilitation and Recreation, 2022)
The purpose is to determine the impact of physical activity on the functional state of applicants duringthe semester. Material and methods. The study involved 116 future water transport specialists. KG –58 graduates of the Faculty of “Navigators” I year (studied in the usual program of physical education);EG – 58 students of the first year of HDMA of the Faculty of Ship Energy – 6 hours (4 hours of electives)per week, according to a specially developed methodology, which included exercises in athletic gym-nastics, table tennis, badminton, theoretical material on the impact of physical activity). The followingresearch methods were used: analysis of literature sources, determination of functional and reserve capa-bilities of the cardiovascular system (Rufier’s test), mathematical analysis.Results. One of the problems of water transport professionals is maintaining physical health. Due tothe fact that the purpose of the shipping company is to maximize profits and increase its economic perfor-mance through efficient use of the fleet, the issue of “health” is usually guided by the order of the Ministryof Health of Ukraine No. 347 “On approval of eligibility rules for the state of health of persons for work onships”. Also, safe navigation on the basis of health on ships is defined as the professional activity of sea-farers, taking into account harmful and dangerous working conditions that do not pose a danger to people,material objects and the environment. As a seafarer is a “seasonal” worker on the ships of foreign ship-owners, his health problems are solved on a purely individual basis. The professional activity of seafarerson ships is associated with the action of harmful factors for a long time without significant interruptions,insufficient access to medical care during the passage of the sea, restrictions on changes in the fleet duringthe voyage, etc. Special conditions of navigation contribute to the occurrence of injuries and the devel-opment of diseases that lead to disability, hospitalization, return to the mainland and dismissals. Giventhe large amount of educational material, limited training time and rather strict international requirementsfor the professional training of seafarers, the modern system of education does not provide explanato-ry and preventive work among higher education seekers regarding the future specifics of their profes-sion in terms of health and effective employment longevity. Health can be viewed from the standpointof the body’s ability to adapt to environmental conditions. The process of adaptation is aimed at maintain-ing homeostasis (stability). However, adaptation in the life of a water transport specialist, in contrast to a simple adaptation, is understood as his active interaction with professional factors and the social envi-ronment of the crew in order to achieve optimal levels of interaction on the principle of homeostasis. Thestudy used the definition of functional and reserve capabilities of the cardiovascular system (Rufier’s test).The data convincingly show an increase in the level of physical performance in EG: 10 % good level (atthe beginning of the experiment – 0); 67.6 % – satisfactory level (60 %); bad – 20 %, remained unchanged;2.4 – unsatisfactory level (20 %). Slight increase in indicators of the level of physical fitness in CG: wellincreased from 7.1 % to 8 %; satisfactory 42.9 % – 43 %; bad 42.9 % – 43.8 %; unsatisfactory 7.1 %decreased to 5.2 %. In fact, the Rufier test makes it possible to assess not only physical performance, fitnessand functional reserve of the heart, but also provides important information about the course of adaptiveprocesses in adapting to physical activity.Conclusions. The study found a positive effect of physical activity on the health of freelancers. Thelevel of physical performance in EG increased: 10 % good level (at the beginning of the experiment – 0);67.6 % – satisfactory level (60 %); bad – 20 %, remained unchanged; 2.4 – unsatisfactory level (20 %).Slight increase in indicators of the level of physical fitness in CG: well increased from 7.1 % to 8 %; sat-isfactory 42.9 % – 43 %; bad 42.9 % – 43.8 %; unsatisfactory 7.1 % decreased to 5.2 %. Thus, it can bestated that motor activity is crucial in shaping the life competence of student youth in the context of the the-ory of life. Restriction of specially organized physical activity is one of the leading factors in reducingthe physical fitness of student youth and their health reserves.